Profiles of positive changes in life outcomes over the COVID-19 pandemic in Chinese adolescents: the role of resilience and mental health consequence - Jian-Bin Li; Kai Dou; Zi-Hao Liu (BMC, 2022)
Abstract Background The 2019 coronavirus (COVID-19) has caused enormous negative impacts on adolescents' routines, social interaction, interpersonal relationships, psychosocial well-being, and physical health. Nevertheless, theories suggest that individuals also often seek out solutions that may facilitate positive changes when they are faced with uncertainty and crisis. However, the existing literature has disproportionately focused on the negative effect of COVID-19 on adolescents, and scant research has examined to what extent and in what aspects adolescents would experience positive changes in times of the pandemic. This pre-registered research aims to bridge said gaps by: (1) exploring different profiles of positive changes in various life outcomes in Chinese adolescents over the COVID-19 pandemic; (2) examining the role of resilience in differentiating different profiles; (3) comparing adolescents' mental health across profiles. Method Participants were 2,567 adolescents aged 12 to 24 recruited from 32 provinces in mainland China (66.89% females; Mage = 19.87 years, SD = 2.02). Through an online survey, participants rated how much their lives of different domains had experienced positive changes since the outbreak of the pandemic. They also answered standardized questionnaires that measured their resilience and mental health. Results Results of latent profile analysis revealed three profiles: limited positive changes (33.3%), partial positive changes (49.5%), and overall strong positive changes (17.2%). Moreover, adolescents with a higher level of resilience were more likely to be categorized into the partial positive changes profile compared to the limited positive changes profile and categorized into the overall strong positive changes profile compared to the other two profiles, after controlling for multiple covariates. Adolescents in the overall strong positive changes profile had better mental health than their counterparts of the other two profiles. Conclusion Chinese adolescents appear to experience positive changes in various life outcomes during the COVID-19 pandemic, especially for those with high levels of resilience. Such positive changes have important implications on adolescents' mental health.